Cover Feature: Water Oxidation Electrocatalysis with a Cobalt‐Borate‐Based Hybrid System under Neutral Conditions (Chem. Eur. J. 41/2018). Issue 41 (5th July 2018) - Turhan, Emine A.; Nune, Satya Vijaya Kumar; Ülker, Emine; Şahin, Ufuk; Dede, Yavuz; Karadas, Ferdi
Abstract : The electrocatalytic water oxidation performance of a new cobalt‐based catalyst, Co3 (BO3 )2, with a Kotoite‐type crystal structure was investigated at neutral pH. Hybridization of the catalyst with carbon nanotubes (CNTs) improved the electrocatalytic properties significantly. Comprehensive electrochemical studies and multi‐reference quantum chemical calculations were performed to study the nature of active cobalt sites as well as the effect of borate coordination to the activity of cobalt ions. More information can be found in the Full Paper by E. Ülker, Y. Dede, F. Karadas, et al. onpage 10372 .